Quality improvement initiative: enhanced communication of newly identified, suspected GI malignancies with direct critical results messaging to surgical specialist. Issue 2 (4th October 2012) - Browning, Travis; Kasper, Jared; Rofsky, Neil M; Camp, Geoffrey; Mang, John; Yopp, Adam; Peshock, Ronald
Abstract : Purpose: To improve timely evaluation and management of newly identified, suspected, gastrointestinal (GI) malignancies discovered on radiologic imaging at a safety-net hospital through direct critical results messaging to surgical specialists. Materials and Methods: To address delays in evaluating patients for suspected GI malignancies identified on imaging, an enhanced workflow was created–electronically routed critical results messaging to the ordering provider was supplemented with parallel messaging to the surgical oncology clinic. Messaging data obtained for 10 months pre and post intervention were compared. Using chart reviews, time intervals were recorded to assess the impact on (1) being seen by a specialist, (2) completing a diagnostic workup and (3) initiating definitive management. Results: Significant improvements were achieved: (1) patients seen by a specialist increased from 45.9% to 98.0% (p<0.001), with median time decreasing from 35 to 7 days (p<0.001); (2) patients completing a diagnostic workup increased from 77.1% to 93.9% (p<0.05), with median time decreasing from 44 to 18 days (p<0.001); (3) patients with initiation of definitive management increased from 72.1% to 89.8% (p<0.05), with median time decreasing from 62 to 35 days (p<0.05). Further study is needed to assess impact on fragmentation of care and financial implications. Conclusions: Direct critical results messaging from the radiologist to the surgical oncologist at a safety-net hospital significantly improves the time to complete a diagnostic workup and initiate definitive management with significantly more patients being seen by a relevant specialist.